Surgical management and postoperative outcomes of orbital cavernous malformations: A systematic literature review by the EANS skull base section - Edoardo Agosti; Vittorio Ricciuti; Giorgio Mantovani; Giorgia De Rosa; Pier Paolo Panciani; Marco Maria Fontanella; Cesare Zoia; Moncef Berhouma; Michaël Bruneau; Luigi Maria Cavallo; Jan Frederick Cornelius; Sebastien Froelich; et al. (Brain and Spine, 2025)
Introduction: Orbital cavernous malformations (OCMs) are benign vascular lesions frequently associated with progressive proptosis and visual disturbances due to their slow growth and compression of adjacent structures. Multiple surgical approaches have been developed for their treatment, including microsurgical transfacial-transorbital approaches (MTTAs), cranio-orbital approaches (MCOAs), orbitotomies (MOs), endoscopic endonasal approaches (EEAs), and endoscopic transorbital approaches (ETOAs). However, the optimal approach remains a topic of debate. Research objective: This systematic review aims to compare the resection rates, postoperative complications, and clinical outcomes across various surgical approaches for OCM management. Methods: A comprehensive literature search was performed in PubMed, Embase, and the Cochrane Library according to PRISMA guidelines. Studies reporting surgical treatment of OCMs with clinical outcome data were included. Study quality was assessed using the Newcastle-Ottawa Scale. Statistical analyses were conducted using chi-square and Mann-Whitney U tests. Results and conclusions: Of 239 screened studies, 94 met inclusion criteria, comprising 1007 patients (mean age 43.9 years; 58.5 % female). Proptosis (63.2 %) and visual impairment (48.1 %) were the most common symptoms. Most lesions were intraconal (80 %) and laterally positioned (42.8 %). EEAs were the most commonly used approach (40.1 %), followed by MOs (25.7 %) and MTTAs (21.6 %). Gross total resection was achieved in 93.7 % of cases. Complications were infrequent: visual acuity worsening (3.9 %), diplopia (2.4 %), and enophthalmos (1.7 %). Functional outcomes improved significantly, particularly visual acuity (65.1 %) and proptosis (61.6 %). EEAs provide high resection rates with minimal morbidity, especially for medial OCMs. ETOAs represent a promising, minimally invasive option for laterally located lesions.